Open Science, the alliance way: Connecting institutional efforts through the EUTOPIA European University - Stoy, Lennart; Kotar, Mojca; Losada, Marina; Casaldàliga, Anna (Septentrio Conference Series, 2022)
Universities are challenged with creating an enabling environment for Open Science, including policies, technical infrastructure, services, training and support and cross-cutting issues such as FAIR research data management and Open Access. In many universities, staff and skills to supply are in high demand and the level of implementation is often lower than the strategic importance given to Open Science (EUA, 2021). Collaboration is crucial to address these challenges, be efficient and avoid duplication of efforts across higher education institutions and other stakeholders. European university alliances are one mechanism that supports such collaborations (Council of the EU, 2021). In the EUTOPIA European University, an alliance consisting of 10 member universities from across Europe, an ambitious work programme has been developed and is implemented through several projects funded by Erasmus+ and Horizon 2020. EUTOPIA understands Open Science as a core pillar, recognizing that knowledge needs to be accessible for everyone. Therefore, our alliance aims to mainstream Open Science across the network and create closer policy alignment between individual alliance members. We do so by addressing different dimensions relevant for Open Science, from policies over to joint training and support, as well as coordinating these activities across the alliance and policy alignment (implemented in a subsidiary way). Overall, our activities cover: Building technical infrastructure, although challenging across institutional and national boundaries, through a collaboration with OpenAIRE. This will facilitate FAIRness of our research results and FAIR-compliance of institutional repositories. Training and guidance on crucial issues such as research data management, Open Access, Citizen Science, and reproducible research for different target audiences. A framework policy for research assessment & metrics considering Open Science as a cross-cutting issue. Citizen science receives special attention through the establishment of a community of practice and regular citizen science clinics, informal meet-ups to share experience, approaches and challenges in Citizen Science. A template Open Science policy to be implemented in modular fashion by partner universities and the creation of an alliance-wide Open Science office. In short, European Universities are an important vehicle for connecting Open Science expertise and capacity across higher education institutions. They allow for the integration and efficient use of local expertise and networks for the benefit of the academic community of all members. Moreover, they are platforms for experimentation and sharing experience among partners with a focus on producing tangible results and improvements. We believe that alliances such as EUTOPIA are important tools to advance Open Science in Europe.